Pengaruh Customer Perceived Value Terhadap Loyalitas Tamu Di Grand Basko Hotel Padang - Ridho Putra Dewahyudi; Rian Surenda; Nova Shabrina (Departemen Pariwisata Universitas Negeri Padang, 2026)
Amid intensifying hospitality competition in Padang City, this study set out to determine how strongly customer perceived value drives guest loyalty at Grand Basko Hotel Padang. A causal associative design under a quantitative descriptive framework was chosen, drawing on 100 guests selected as respondents through purposive sampling. A previously validated and reliable Likert-scale questionnaire served as the data-collection tool, with the resulting data processed via descriptive analysis and simple linear regression in SPSS version 27. The analysis places both customer perceived value and guest loyalty within the very good category, at average scores of 4.26 and 4.29 respectively. Hypothesis testing further establishes that customer perceived value carries a positive, significant effect on guest loyalty (t = 17.982; sig. = 0.000 < 0.05), explaining 76.7% of the variance (R Square = 0.767), with the remaining 23.3% attributable to factors outside this study's scope. In short, stronger perceived value among guests translates into stronger loyalty. Grand Basko Hotel Padang's management is accordingly encouraged to keep reinforcing customer perceived value, particularly through service quality and the guest experience, so that guest loyalty is sustained over time.